SHADOWS IN YOUNG MINDS: IDENTIFYING SUICIDE RISK IN ADOLESCENTS (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2026)
The escalating rate of adolescent suicide represents a profound global public health crisis that demands immediate and innovative intervention strategies. As traditional clinical assessments often fail to capture the dynamic and multifaceted nature of suicidal ideation, computational methods have emerged as a vital supplementary tool. This paper proposes a comprehensive, multimodal machine learning framework designed to identify suicide risk in adolescents by integrating clinical health records, acoustic speech features, and linguistic markers from digital platforms. By synthesizing diverse data modalities and applying semi-supervised learning techniques, this approach aims to overcome the limitations of isolated datasets and provide a more robust, real-time assessment of patient vulnerability. Ultimately, the integration of advanced predictive models into psychiatric care holds the potential to facilitate timely interventions, reduce the cognitive burden on crisis responders, and save young lives